The War-related Impacts on Tourism in Neighbouring Countries: Poland in the Face of the War in Ukraine - Kiczmachowska, Ewa E. (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: In contrast to countries directly involved in military conflicts or terrorism, where the impact on tourism has been always reported negatively, the conclusions for neighbouring countries were not entirely unequivocal: they either suffered from the proximity of warfare or benefited from a spill-over effect. The purpose of this research is to assess how war affects tourism in a neighbouring country with regard to the tourism crisis management framework, the fundamental motives framework, and consumer choice theory.Research Design & Methods: The research was based on quantitative analysis of 29 variables (macroeconomic indicators, international and domestic tourist flows, refugee influx) for the first ten months of the conflict with respect to the hospitality sector in Poland.Findings: The consequences of the war in Ukraine have not led to a decline in the intensity of tourism in Poland in the short term. The mix of foreign tourist flows combined with no significant effects on domestic travel, has resulted in a surprisingly stable performance.Implications / Recommendations: No short-term decline in tourism intensity is a valuable insight for participants in the tourism sector, as it allows them time to adjust. However, sharp increases in energy and fuel costs along with inflation, constitute a threat to domestic demand in the longer term.Contribution: While the war or postwar issues appear frequently in tourism literature in relation to countries directly involved, the research on neighbouring countries is rare. In contrast to previous research, this paper focused on a neighbouring country with tourism claiming a relatively low share of GDP and included direct and indirect war impacts.